Networked graphics : building networked games and virtual environments - Steed, Anthony (Morgan Kaufmann ; Elsevier Science [distributor], 2009)
This broad-ranging book equips programmers and designers with a thorough grounding in the techniques used to create truly network-enabled computer graphics and games. Written for graphics/game/VE developers and students, it assumes no prior knowledge of networking. The text offers a broad view of what types of different architectural patterns can be found in current systems, and readers will learn the tradeoffs in achieving system requirements on the Internet. The book explains the foundations of networked graphics, then explores real systems in depth, and finally considers standards and extensions. Numerous case studies and examples with working code are featured throughout the text, covering groundbreaking academic research and military simulation systems, as well as industry-leading game designs. Everything designers need to know when developing networked graphics and games is covered in one volume - no need to consult multiple sources. The many examples throughout the text feature real simulation code in C++ and Java that developers can use in their own design experiments. Case studies describing real-world systems show how requirements and constraints can be managed.